Transport and AC Impedance Studies of Plasticized-Chitosan Based Polymer Electrolytes - A.S.A Khiar; A.K. Arof (Institut Teknologi Bandung, 2011)
Dimethyl Carbonate (DMC)-plasticized chitosan-based polymer electrolytes were prepared in the present work. The sample 37.5 wt% chitosan - 37.5 wt% NH4CF3SO3 - 25 wt% DMC showed the highest conductivity of (1.95±0.15) x 10-6 S/cm. From calculated values obtained using the Rice and Roth model, the increase in conductivity is due to the increase in the number density of mobile ions. Universal Power Law was used to analyze the AC conductivity of the sample. Arrhenius behavior was observed in the plot of hopping frequency; ωP against temperature. The AC conductivity master curve was obtained for the highest conducting sample when scaled vertically by σ and horizontally by ω .